Antibacterial Potential of Cocos nucifera Coir Extract and Green Synthesis of Silver Nanoparticles - Akkalkote, Rajashri; Dhuttargi, Priyanka; Homkar, Komal; Shivsharan, Rohini; Ayyar, Priya; Patil, Vikas (Journal of Sustainability and Environmental Management, 2025)
Since ancient times, humans have used medicinal plants due to their therapeutic properties as the main source of drugs. Because plant extracts have various biological properties, such as anthelminthic, anti-inflammatory, antioxidant, antifungal, and antitumor. Cocos nucifera, which is commonly called the coconut tree, is a widespread plant across the world. Its easy availability makes it easy to use. The study aimed to evaluate the antibacterial activity of Cocos nucifera extract against bacterial pathogens and to test the phytochemicals using simple chemical qualitative tests. The acetone extract of Cocos nucifera coir was prepared using the Soxhlet method. The research showed that the extract contained Saponin, Tannin, Cardiac Glycosides and Flavonoids. The antibacterial assay revealed antibacterial activity in the plant extract, as it was effective against the test organisms. The extract showed the ability to produce silver nanoparticles. The synthesised silver nanoparticles were characterised using UV-visible spectroscopy, FTIR, and XRD. The presence of various phytochemicals in plants suggests their use in folk medicine. The antibacterial properties of the extract suggest it has a wide range of applications across diverse fields.